2006
DOI: 10.1208/aapsj080114
|View full text |Cite
|
Sign up to set email alerts
|

Opioid ligands with mixed μ/δ opioid receptor interactions: An emerging approach to novel analgesics

Abstract: A BSTRACTOpioids are widely used in the treatment of severe pain. The clinical use of the opioids is limited by serious side effects such as respiratory depression, constipation, development of tolerance, and physical dependence and addiction liabilities. Most of the currently available opioid analgesics exert their analgesic and adverse effects primarily through the opioid receptors. A large number of biochemical and pharmacological studies and studies using genetically modifi ed animals have provided convinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 56 publications
5
112
0
2
Order By: Relevance
“…As has been reported [8][9][10][11][12][27][28][29] by several research groups, including ours, that k agonists with m partial agonistic or antagonistic activities are more efficacious than the pure k agonists in treating several CNS disorders, especially drug abuse, several compounds in our current studies, such as thiazole 8 and imidazo[2,1-b]thiazoles 10 and 11, which have agonistic activity at the k and partial agonistic or antagonistic activities at m receptors, are worthy of further investigation.…”
Section: Resultssupporting
confidence: 52%
“…As has been reported [8][9][10][11][12][27][28][29] by several research groups, including ours, that k agonists with m partial agonistic or antagonistic activities are more efficacious than the pure k agonists in treating several CNS disorders, especially drug abuse, several compounds in our current studies, such as thiazole 8 and imidazo[2,1-b]thiazoles 10 and 11, which have agonistic activity at the k and partial agonistic or antagonistic activities at m receptors, are worthy of further investigation.…”
Section: Resultssupporting
confidence: 52%
“…These include the development of partial activators of the µOR (ref. 4); of compounds that activate the µOR but block other opioidreceptor subtypes 5 ; and of compounds that are restricted to the peripheral, rather than the central, nervous system 6 . Other approaches have involved molecules that bind to the µOR only in acidic environments 7 (which are often associated with damaged tissue), and compounds that target opioid receptors formed from more than one subtype 8 .…”
Section: Strategy For Making Safer Opioids Bolsteredmentioning
confidence: 99%
“…More than 150 estimates of equilibrium climate sensitivity (ECS) have been published 3 , many of which suggest that worryingly high sensitivities are possible -including one that was published in Nature just a few weeks ago 4 . On page 319, Cox et al 5 use an ingenious approach to rule out high estimates. If correct, this would improve the chances of achieving internationally agreed targets for minimizing global warming.…”
Section: P I E R S F O R St E Rmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Ananthan extended these studies to a non-peptidic dual profile ligand 2, but the results are difficult to interpret due to low mu opioid agonist efficacy and potency, and the need to administer the drug icv. 6,8 As part of our studies into developing non-peptide ligands with a dual profile of potent mu opioid agonism and delta opioid antagonism as potential analgesics lacking tolerance and dependence, we previously reported that the presence of a 6,7-fused indolic group does not necessarily result in delta opioid selectivity. 9 This is in contrast to accepted structure-activity relationships, where the indole is considered responsible for delta selectivity.…”
mentioning
confidence: 99%